Cutting-edge communication and learning assistive technologies for disabled children: An artificial intelligence perspective - Zdravkova, Katerina; Krasniqi, Venera; Dalipi, Fisnik; Ferati, Mexhid (Frontiers in Artificial Intelligence, 2022)
In this study we provide an in-depth review and analysis of the impact of artificial intelligence (AI) components and solutions that support the development of cutting-edge assistive technologies for children with special needs. Various disabilities are addressed and the most recent assistive technologies that enhance communication and education of disabled children, as well as the AI technologies that have enabled their development, are presented. The paper summarizes with an AI perspective on future assistive technologies and ethical concerns arising from the use of such cutting-edge communication and learning technologies for children with disabilities.